Intelligent and interactive household simulation for energy management algorithms` evaluation = Inteligentna i interaktywna symulacja domostw do testowania algorytmów zarządzania energią - Koropiecki, Igor; Powroźnik, Piotr; Piotrowski, Krzysztof (Zielona Góra: Uniwersytet Zielonogórski, Instytut Metrologii, Elektroniki i Informatyki)
This work describes the progress towards creating a tool for simulating households for evaluation of energy management techniques. Proper evaluation in this area is costly, time consuming and additionally error prone due to human factors. The proposed approach aims at replacing the real users and their devices with simulated ones, but with achieving results as close to reality as possible. Further, it offers flexibility, usually not available in real test scenarios.
Keywords: komputeryzacja; przyrządy pomiarowe; informatyka; technologie informacyjne